Analysis of Pranata Computer’s Data Governance Activities based on DAMADMBOK 2 - Alivia Yulfitri; Yunita Fauzia Achmad (Jurnal Rekayasa Sistem & Industri, 2020)
Until now, the government is very difficult to get data that is valid, accurate, reliable, and easily accessible.Often there are differences in data, between ministries, government agencies, state-owned companies,private companies, or others. This has become a constraint for leader in decision making. At the end of2018, the Government plans to establish a Presidential Regulation concerning the One Data Indonesia, butuntil now (2019) has not yet. One of the critical success factors for this initiative is human resources (HR),namely Pegawai Negeri Sipil (PNS) who have functional positions as Pranata Komputer (PK). PK has taskand function of planning and managing information technology in the government. This research aims toanalyze PK activities related to data management based on DAMA-DMBOK 2. The methods used aredocument collection, assessment, analysis of DAMA-DMBOK 2 activities and current activities, andmapping of PK activities and data management, which focus on three knowledge (data governance, dataquality management, and metadata). The output is the mapping of PK activities based on DAMA-DMBOK2. The results of research can be used as a reference for evaluating and improving regulations related toPranata Komputer activities that support the implementation of data governance in government.